Outline of a perspective model of the link of the open communication of the system of phase synchronization of modern telecommunications - Козловський, В. В.; Туровський, О. Л.; Кулінський, В. Д. (Science-based technologies, 2020)
The paper considers the issues of substantiation of the outline of a promising model of the open link of the phase synchronization system of modern telecommunications. Substantiation of the outline and development of the necessary mathematical model of the link of open communication in the work is carried out under the following conditions: maintaining high system speed; ensuring higher-order astatism of the system; possibilities for minimizing the phase error variance of the phase synchronization system; opportunities to implement the developed mathematical model of the open link on the existing element base. The synchronous-phase demodulator scheme was chosen as the initial scheme for further modeling of the open communication link with the necessary properties in the work. The obtained and presented mathematical dependences of the transfer function of the synchronous-phase demodulator with open connection allow to maintain the order of astatism of the system equal to two and provide the necessary dynamics of the phase synchronization system in constant modes of carrier frequency estimation. The mathematical model of the proposed transfer function can be implemented on microprocessors and has the ability to its preliminary analysis on computers without prior integration operations and approximate calculation of transition matrices. A further direction of research initiated in this work is the synthesis of open communication in synchronous-phase demodulators with a higher order of astatism in the transient modes of operation of the phase synchronization system.